Polyconvolution formation of finite integral transformations - Kakichev, V. A. (Mathematical Modelling and Analysis, 1997)
“Polyconvolution formation of finite integral transformations” Mathematical Modelling Analysis, 2(1), p. 79-83. First Published Online: 14 Oct 2010